Outcome Based Education pada Kurikulum Merdeka: Tantangan dan Peluang dalam Pendidikan Agama Islam - Manggali, Cahya Arrum; Hayati, Dina Nur; Mundofi, Ahmad Asron (Nusantara: Jurnal Pendidikan Indonesia, 2024)
Purpose – The purpose of this research is to analyze the challenges and opportunities of Outcomes-Based Education (OBE) based independent learning curriculum in the scope of PAI.Method – The method in this study employs a qualitative research type with a library research approach. For data analysis, the author uses the guidelines from Miles and Huberman, which include data collection, data reduction, and conclusion drawing. The validity of the data is checked using the content check point technique, a method used to verify the accuracy of each piece of information that forms the basis for drawing conclusions.Findings – The results of this study indicate that there are opportunities that can be found in the scope of PAI, including increasing curriculum relevance, the development of clear learning outcomes, emphasizing practical skills, competency-based evaluation, collaborative program development, project-based improvement, using technology in learning, self-evaluation and continuous improvement, integrating soft skills, and improving the quality of graduates. In addition, there are several challenges associated with the implementation of OBE at the tertiary level, including difficulties in finding measurable learning outcomes, paradigm shifts, adjustments to institutional culture, limited resources, difficulties in measuring spiritual and moral competencies, integration with Islamic educational traditions, challenges in developing assessment instruments, difficulties in developing effective learning plans, students' understanding of new approaches, and dealing with student diversity. Research Implications – This research implies that the implementation of Outcome-Based Education (OBE) in Islamic Religious Education in higher education brings several opportunities that can increase the effectiveness and relevance of Islamic Religious Education.